Influence of Number of Pole Pairs on Torque Ripple of Magnetic Gear - Huang Zhangxian; Jing Libing (Jixie chuandong)
The field modulation magnetic gear is a kind of transmission device with broad development prospects. It has the advantages of no friction， no pollution， less maintenance and easy installation. The magnetic gear models with different transmission ratio are established. The input and output torque waveforms of different models are compared. The influences of the number of pole pairs of inner rotor （P1） and the number of pole pairs of outer rotor （P2） on torque ripple are analyzed. According to the principle of magnetic field modulation and spatial magnetic field harmonic distribution， the torque ripple of magnetic gear is greatly affected by P1 and P2. The research results show that the torque ripple can be effectively reduced by selecting the magnetic gear with P1=4， P1:P2=1:n+0.25 or 1:n+0.75 （n is a natural number）.